Spatio-temporal survey of small mammal-borne Trypanosoma lewisi in Cotonou, Benin, and the potential risk of human infection - (:unkn) unknown (My University, 2019)
Highlights: • A Trypanosoma survey was conducted in 369 small mammals from districts of Cotonou, Benin, during three successive seasons. • Sequencing data allowed us to unambiguously identify Trypanosoma lewisi in 144 parasitized animals. • Prevalences range between 39.2% (qPCR only) and 57.2% (individuals for which sequences were obtained). • Trypanosomes were identified in all but one mammalian species; Rattus rattus was more infected than the other hosts. • No difference in prevalence was found neither between seasons nor districts. • Our data and local socio-environmental conditions suggest a high risk of trypanosomes spill-over from rodents to human.Abstract: Human trypanosomoses are the sleeping sickness in Africa and Chagas disease in Latin America. However, atypical human infections by animal trypanosomes have been described, but poorly investigated. Among them, the supposed rat-specific T. lewisi was shown to be responsible for a few severe cases. In Africa, the scarcity of data and the null awareness about the atypical human trypanosomoses suggest that the number of cases may be higher that currently thought. Furthermore, T. lewisi is resistant to normal human serum and therefore a po-tential human pathogen. In order to document T. lewisi distribution and ecology, a qPCR- and 16DNA sequen-cing-based survey was conducted in 369 rodents from three urban districts of Cotonou city, Benin, during three different periods of the same year. Our study demonstrated very high prevalence (57.2%) even when considering only individuals identified as positive through DNA sequencing (39.2%). Black rats represented the most dominant as well as the most T. lewisi-parasitized species. No diffrence was retrieved neither between seasons nor districts, suggesting a large infestation of rodents by trypanosomes throughout the year and the city. Our results suggest that conditions are gathered for rat to human transmission of T. lewisi
Keywords: African Research